The rise of Mormonism - Stark, Rodney (Columbia University Press, 2005)
Will Mormonism be the next world faith, one that will rival Catholicism, Islam, and other major religions in terms of numbers and global appeal? This was the question Rodney Stark addressed in his much-discussed and much-debated article, ""The Rise of a New World Faith"" (1984), one of several essays on Mormonism included in this new collection. Examining the religion's growing appeal, Rodney Stark concluded that Mormons could number 267 million members by 2080. In what would become known as ""the Stark argument, "" Stark suggested that the Mormon Church offered contemporary sociologist.